The use of objective structured clinical examination to assess cardiopulmonary resuscitation at the surgical center (Research, Society and Development, 2020)
The objective is to evaluate the assimilated skills and compare them to the knowledge retained after training by the nursing staff of the surgical center about cardiopulmonary resuscitation. Method quantitative, quasi-experimental approach, of the pre and post type, organized in two phases. In the first, there was the application of the pre-test to assess previous knowledge, and later theoretical-practical class on the subject. After 3 months, the second phase was carried out, application of the post-test and tool to assess practical skills. Statistical programs were used: SPSS and R 3.6.3, univariate and bivariate analyzes were performed, in addition to the Wilcoxon test and Spearman correlation. 31 professionals participated in the two stages, with a predominance of nursing technicians (96.7%) and female (97.1%). The nurse had a higher total score (6.5) than the technicians (4.1 ± 1.33). The 37-46 age group also stood out from the rest (5.1 ± 0.82). The professionals showed assimilation of knowledge after the intervention, evidenced by improvement in the post-test (p-value: 0.002). Regarding skills, the main difficulties and inadequacies found were in compressions (3.4 ± 1.15) and ventilation (1.7 ± 0.58). The intervention proved to be an effective strategy for improving the team's knowledge and skills. However, they need periodic training, for updates and continuing education, since there is a decrease in the knowledge retained over time. The correct execution of cardiopulmonary resuscitation correctly contributes directly to the patient's survival.